Frightened of the pulp? A qualitative analysis of undergraduate student confidence and stress during the management of deep caries and the exposed pulp. (5th October 2020) - Chevalier, V.; Le Fur Bonnabesse, A.; Duncan, H. F.
Abstract: Aim: To evaluate sources of student confidence and stress during the management of deep carious lesions and the exposed pulp during undergraduate clinics. Further aims were to identify barriers and facilitators, which could result in educational or practical improvements in the delivery of teaching and provision of treatment in this area. Methodology: A exploratory qualitative study design was used, based on recorded focus group interviews, guided by 12 predetermined questions. The discussions were transcribed verbatim and analysed by inductive qualitative content analysis. Common categories were identified to aid understanding. Forty undergraduate dental students from 4th and 5th years in Dublin Dental University Hospital participated in the study. Results: Student stress and confidence were multifactorial and broadly linked to specific domains: clinical procedure, academic education, clinical training, evaluation/grading, organization and equipment, vital pulp biomaterial and the patient. Most students expressed a preference for one‐stage selective carious removal to soft dentine rather than potential pulp exposure in deep carious lesions, noting that although it helped to decrease their immediate stress, it also caused longer‐term concern by leaving caries close to the pulp. Nevertheless, their confidence was affected by limited clinical experience of carrying out selective removal procedures in deep caries. A recurrent finding was students citing high levels of stress after pulp exposure. Feelings including anger, fear, embarrassment and denial were associated with pulp exposure during deep caries management. Generally, the students felt able to manage pulp capping procedures, but were less certain about partial pulpotomy, suggesting that although they are aware of its advantages, they were unsure about the appropriate volume of pulp tissue to remove. To reduce stress, students suggested that laboratory teaching should employ new 3‐D printed solutions and clinics should establish clear consensus amongst supervising teachers about the best way to manage the exposed pulp. Conclusions: Students lacked confidence as they neared the pulp and prefer selective caries removal techniques, which reduce the likelihood of pulp exposure. Students identified stressors and suggested improvements in several domains that would improve confidence. These ameliorations could lead to enhancements in student ability to perform these conservative techniques, and improve the provision of treatment in this area.